Retrodicting large herbivore biomass for the last glacial maximum on the Palaeo-Agulhas Plain (South Africa) using modern ecological knowledge of African herbivore assemblages and rainfall. (November 2021) - Brooke, Christopher F.; Marean, Curtis W.; Wren, Colin D.; Fritz, Hervé; Venter, Jan A.
Abstract: Herbivore distribution throughout Africa is strongly linked to mean annual precipitation. We use that relationship to predict functional group composition of herbivore communities during the last glacial maximum (ca. 21 ka) on the now submerged Palaeo-Agulhas Plain (PAP), South Africa. We used metabolic large herbivore biomass (MLHB) from 39 South African protected areas, in five functional groups (characterized by behavior and physiology). We examined how modern factors influenced MLHB and considered the effects of biome, annual rainfall, percentage winter rainfall, and protected area size. Overall, biome was the most important factor influencing the relationship between MLHB and rainfall. In general, MLHB increased with rainfall, but not for the grassland biome. Outside grasslands, most functional groups' metabolic biomass increased with increasing rainfall, irrespective of biome, except for medium-sized social mixed feeder species in savanna and thicket. Protected area size was influential for medium-sized social mixed feeders and large browsers and rainfall influenced medium-sized social mixed feeders, offering some perspectives on spatial constraints on past large herbivore biomass densities. These results improve our understanding of the likely herbivore community composition and relative biomass structure on the PAP, an essential driver of how early humans utilized large mammals as a food resource.